PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, PROMOSI, CITRA MEREK DAN CELEBRITY ENDORSER TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Konsumen Daia di Kota Semarang) - Fauzul Munna, 15.05.51.0262; Maskur, Ali (Students' Journal of Economic and Management, 2019)
The purpose of this study was to examine and analyze the effect of product quality, price perception, promotion, brand image and celebrity endorser on the decision to purchase Daia laundry soap. This research was conducted in the city of Semarang The population in this study is consumers who have used and bought Daia in the city of Semarang. The sampling technique used in this study was purposive sampling with a total sample of 105 respondents. This study uses primary data with data collection techniques, namely questionnaires and interviews. Data were analyzed using validity test, reliability test, multiple regression analysis, F test, determination coefficient test (R2), t test, which was then processed using the SPSS 19 computer program. The results showed that product quality had a positive and insignificant effect on purchasing decisions. Price perception has a positive and significant effect on purchasing decisions. Promotion has a positive and significant effect on purchasing decisions. Brand image has a positive and not significant effect on purchasing decisions. Celebrity endorsers have a positive and significant effect on purchasing decisions.